Extranodal presentation of Hodgkin's lymphoma of the sternum: A case report and review of the literature - Li, Yan (Oncol Lett, 2018)
Hodgkin's lymphoma (HL) is typically a systemic disease with involvement of the cervical, supraclavicular and mediastinal lymph nodes. An extra-nodal presentation of HL is unusual and seldom encountered in the clinic. The most common sites of presentation for extra-nodal extension are the spleen, liver, lungs, bones and marrow. The bones that are frequently involved are the vertebrae, pelvis, ribs and femur. Involvement of the sternum has occasionally been reported. The current study presents an unusual case on the extra-nodal presentation of HL of the sternum arising in a 25-year-old woman, and reviews the relevant literature with particular emphasis on treatment. The extra-nodal infiltration of HL, and the clinical stage and prognosis of the case are also discussed.